Forecasting indicators of the fluid catalytic cracking process of vacuum gas oil with the involvement of different ratios of selective oil extract; Химия и химическая технология в XXI веке; Т. 2 - Nafo B. J. (Химия и химическая технология на иностранном языке (английский), 2023)
Заглавие с титульного экрана